Beta‐blocker therapy is not associated with mortality after intracerebral hemorrhage. (4th September 2017) - Sykora, M.; Putaala, J.; Meretoja, A.; Tatlisumak, T.; Strbian, D.
Abstract : Background: Beta‐blocker therapy has been suggested to have neuroprotective properties in the setting of acute stroke; however, the evidence is weak and contradictory. We aimed to examine the effects of pre‐admission therapy with beta‐blockers (BB) on the mortality following spontaneous intracerebral hemorrhage (ICH). Methods: Retrospective analysis of the Helsinki ICH Study database. Results: A total of 1013 patients with ICH were included in the analysis. Patients taking BB were significantly older, had a higher premorbid mRS score, had more DNR orders, and more comorbidities as atrial fibrillation, hypertension, diabetes mellitus, ischemic heart disease, and heart failure. After adjustment for age, pre‐existing comorbidities, and prior use of antithrombotic and antihypertensive medications, no differences in in‐hospital mortality (OR 1.1, 95% CI 0.8‐1.7), 12‐month mortality (OR 1.3, 95% CI 0.9‐1.9), and 3‐month mortality (OR 1.2, 95% CI 0.8‐1.7) emerged. Conclusion: Pre‐admission use of BB was not associated with mortality after ICH.